Geography Of The Family, Theoretical Aspects, And Qualitative Approaches: An Introduction - Marques Martins, Isis do Mar (Geografares, 2022)
The studies in Geography of the Family are large and involves many analysis in the Geography produced by the so called Global North, in spite of a few Latin-American references. This paper is a systematization of these analysis and attempt to overcome the orthodox way of the Geography of the Family’s comprehension under classical and neoclassical theories, also proposing new approaches from the Brazilian context. It results in a necessary effort to think new perspectives in spatial analysis.